Laser induced PT -symmetry breaking in the fluctuations of electronic fluids - Aquino, Rui [UNESP]; Silvano, Nathan O.; Barci, Daniel G. (American Physical Society (APS), 2024)
Electronic fluids can display exciting dynamical properties. In particular, due to Landau damping, the collective-mode spectrum of an electronic system with multipolar interactions is non-Hermitian, and can present non-Hermitian degeneracies called exceptional points. In this work, we want to explore the dynamical properties of these degeneracies using laser control. We show that by using a light pulse, we can control the collective-mode spectrum and tune a non-Hermitian PT phase transition in which two exceptional points annihilate each other. At this transition, the gap closes with a cubic root signature, which defines a third-order exceptional point.